(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
Subjective Well-Being as a Dynamic Interaction between Individual and Context. Using the perspective of health psychology, the present paper highlights subjective (emotional) well-being is a dynamic construct, resulting from the interaction between internal, individual factors (including how individuals perceive and interpret the world) and the social context in which individuals live and act. Consequently, the way in which the individual adapts to new events and the dimensions of the quality of life depend on a number of factors, such as: cognitive processes, the individual’s temperament and personality, personal values and goals, including spiritual values and involvement in activities that give meaning to life, as well as factors related to the social and cultural context in which the individual lives, the social roles he or she fills, the relationships and social support available to him or her, factors whose influence we will examine in this study.